Analisis Pengaruh Suasana Toko Dan Kualitas Produk Terhadap Minat Beli Konsumen Pada Distro Black Id Kota Bukittinggi - Nurfitriyenni, Nurfitriyenni (Jurusan PIPS FKIP UMMY Solok, 2019)
This study aims to determine the effect of store atmosphere, product quality, and customer satisfaction, on consumer buying interest in Black Id distributions in the city of Bukittinggi. The object of this research is customers who buy branded men's clothing products at Black Id Distro. The sample was selected using the Lemesshow formula with 98 customers as a sample. The type of data used is primary data and secondary data. Data analysis using binary logistics analysts after passing the validity test, reliability test, variable descriptive analysis by using Statistical Package For Social Science (SPSS) program 16.00. Based on the results of the study, the indicators in this study are all valid statement indicators. Data testing with Binary Logistics Collaboration analysts found that the store atmosphere variable (X1), product quality (X2), had a positive and significant influence on consumer buying interest in the Bukittinggi city Black Id distro, both partially and simultaneously viewed from the test results Wald and the G test have significant values ??smaller than 0.05. The most dominant variable in this study is customer satisfaction seen from the results of the B expectations test.